2016
DOI: 10.3398/064.076.0307
|View full text |Cite
|
Sign up to set email alerts
|

Sagebrush, Greater Sage-Grouse, and the Occurrence and Importance of Forbs

Abstract: Big sagebrush (Artemisia tridentata Nutt.) ecosystems provide habitat for sagebrush-obligate wildlife species such as the Greater Sage-Grouse (Centrocercus urophasianus). The understory of big sagebrush plant communities is composed of grasses and forbs that are important sources of cover and food for wildlife. The grass component is well described in the literature, but the composition, abundance, and habitat role of forbs in these communities is largely unknown. Our objective was to synthesize information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…, ; Pennington et al . ) and invigorated efforts for their reestablishment through direct seeding. To date, research into seed dormancy has targeted a narrow range of forb and shrub species restricted to a few genera (Allen & Meyer ; Meyer & Kitchen ; Scholten et al .…”
Section: Introductionmentioning
confidence: 99%
“…, ; Pennington et al . ) and invigorated efforts for their reestablishment through direct seeding. To date, research into seed dormancy has targeted a narrow range of forb and shrub species restricted to a few genera (Allen & Meyer ; Meyer & Kitchen ; Scholten et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although burned areas lack A. tridentata, they provide forage resources (perennial grasses and forbs) that are less abundant elsewhere on the landscape. These could be important for both livestock and sage-grouse (Centrocercus urophasianus) chicks (Pennington et al 2016, Scasta et al 2016. Shrub-free patches also provide grassland bird habitat for lark buntings (Calamospiza melanocorys), western meadowlarks (Sturnella neglecta), and grasshopper sparrows (Ammodramus savannarum) found in mixed-grass prairie with taller vegetation (Augustine and Derner 2015).…”
Section: Implications For Managementmentioning
confidence: 99%
“…Many studies have demonstrated the importance of forbs to Greater Sage-Grouse, providing food both directly and indirectly by supporting insects and providing cover (e.g., Connelly et al 2011;Dumroese et al 2015;Pennington et al 2016). Oregon BLM wildlife biologists have a list of high and moderate value species important to Greater Sage-Grouse that has been refined since the 2015 Final EIS (BLM Sage Grouse Forb List August 2017).…”
Section: Impacts On Vegetation Including Noxious Weeds Riparian Arementioning
confidence: 99%
“…Forb richness and abundance are controlled by site characteristics and climate, with drought a particularly important driver (Blomberg et al 2014;Pennington et al 2016;Blomberg et al 2017;Gibson et al 2017;Pennington et al 2017). Only a few studies have examined forb response to disturbance, such as fire, and even fewer have attempted to correlate forb response to drought status, changes in temperature and precipitation regimes, and soil water availability whether in the absence or presence of grazing (Davies et al 2012a;Davis and Crawford 2015;Ellsworth et al 2016;Pennington et al 2016). A global literature review of the impacts of grazing on grouse species found too few studies that had enough detail concerning animal type, animal distribution, stocking rates, grazing timing, duration, and frequency, and similar factors to develop BMPs for grazing in Greater Sage-Grouse habitat (Dettenmaier et al 2017).…”
Section: Impacts On Vegetation Including Noxious Weeds Riparian Arementioning
confidence: 99%
See 1 more Smart Citation